Effect of Nano Biofertilizer with Spirulina platensis on Vegetative Growth and Nutrient Solution Stability in Floating Raft Hydroponic System of Vegetable Crops - Nurhaidar Rahman; Nonon Saribanon; Puspita Deswina; Rita Noveriza; Nurhamidar Rahman (Journal of Tropical Biodiversity, 2026)
This study aimed to evaluate the effect of nano biofertilizer derived from Spirulina platensis on the vegetative growth of mustard greens (Brassica juncea) and the stability of nutrient solution in a floating raft hydroponic system. The treatments included 100% AB mix solution as control, 100% Spirulina nano solution, and a combination of AB mix + Spirulina nano. The nano biofertilizer was formulated in two particle sizes, namely F1 (±165 nm) and F5 (±380 nm), each tested in combination with nutrient solutions to assess their effectiveness on plant growth and solution stability. Vegetative growth parameters observed were plant height, leaf number, leaf width, leaf length, and chlorophyll content. Solution stability was evaluated through measurements of pH, Electrical Conductivity (EC), and Total Dissolved Solids (TDS/PPM). The experiment was arranged in a randomized block design (RBD) with five treatments and four replications, he results showed that the combination treatment of 50% AB mix + 50% Spirulina nano (particle size F5) produced the best vegetative growth, with plant height reaching ±31 cm at the 6th week, greater leaf number, and higher chlorophyll content compared to other treatments. The 100% Spirulina nano treatment supported plant growth, but the results were still below those of AB mix. Analysis of pH, EC, and PPM indicated that Spirulina nano contributed to maintaining solution stability within the optimal range for hydroponics (pH 5.5–6.5; EC 500–1000 µS/cm). Spirulina nano has potential as an environmentally friendly alternative biofertilizer, either as a partial substitute or as a supplement to hydroponic nutrients, particularly when formulated in appropriate nano particle sizes (F1 and F5) to enhance nutrient absorption efficiency and stability of the floating raft hydroponic system